EFFECT OF THICKNESS OF OVERLAYING CLAY LAYER OF LOWLAND REGION ON SENSITIVITY OF LATERAL DEFLECTION OF LONG PILES EMBEDDED IN NON-HOMOGENEOUS SOIL – PART IIA: NUMERICAL STUDY OF SAND PARAMETERS - D. H. Hafez; B. B. Budkowska (Lowland Technology International, 2006)
This part of the paper is a direct continuation of our first part paper. The first part of the paper presented the theoretical formulation of the sensitivity of the lateral head deflection of piles embedded in non-homogeneous soil consisting of clay overlying sand to changes in the design parameters. The current paper presents numerical sensitivity studies based on this theoretical formulation. The effect of variation in sand parameters on the variation of the lateral head deflection which is an important serviceability measure is studied. Both the clay and pile parameters will be investigated in part IIB of the paper. In lowland areas, the soil profiles starting from the soil surface contain soft clay layer of variable thickness. The effect of the thickness of the overlying clay layer on the sensitivity results is explored through comparative sensitivity assessment. Sensitivity results are given in the form of graphical presentations of sensitivity operators which show along the pile length where and how the change of each design parameter can affect the change of lateral pile-head deflection. It is shown that the thickness of the overlying clay has an effect on changing the magnitude and location of the maximum values of the sensitivity operators.